Feasibility of Automated Prescription by Artificial Intelligence in Telemedicine Based on Health Law - Sebastian, Rommy; Arifin Hoesein, Zainal (Publikasi Indonesia, 2025)
Telemedicine as part of digital health services is officially regulated in Law No. 17 of 2023 concerning Health and implemented through Government Regulation No. 28 of 2024, but has not yet discussed the role of artificial intelligence as a prescription issuing entity. Meanwhile, Law No. 1 of 2024 concerning Electronic Information and Transactions recognizes the validity of electronic documents and digital signatures, opening up legal opportunities for the digitization of medical files. The aim of this study was to evaluate the legal feasibility of automated prescribing by artificial intelligence systems in Telemedicine, in particular reviewing the void of norms governing the